Become more productive by using IPython (O'Reilly Media, 2019)
"If your Python interpreter still starts with>>>, join Jacinda Shelly (Doctor on Demand) to learn how IPython, an enhanced interactive Python shell guaranteed to improve the productivity of any Python user still using the default Python shell, can improve your programming life. And if you've used IPython for a while, stop by to learn tricks you didn't even know IPython had up its sleeve. You'll explore IPython basics and the most productivity-enhancing and some difficult features of IPython, including the most useful IPython commands (e.g., %quickref and help, tab completion, and more); how to configure IPython and its common configurations; magic functions (i.e., anything that starts with % and is awesome); call magics, SciPy magic, and various extensions; and how IPython fits into the Jupyter ecosystem."--Resource description page